IMPROVEMENT OF THE RESULTS OF OPERATIVE TREATMENT OF VARICOSE DISEASE BASED ON THE STUDY OF ULTRASOUND-ANATOMIC FEATURES OF GREAT SAPHENOUS VEIN - Yu. A. Sobolev (Scientific Сentre for Family Health and Human Reproduction Problems, 2012)
150 patients with varicose disease in great saphenous vein system. (GSV) were examined with the help of ultrasound duplex scanning. Location and. quantity of valves and. varicose nodes in GSV were defined, the diameter of supplementary anterolateral and posteromedial inflows was measured and. the location of their confluence into GSV was determined. Comparison of data obtained during the ultrasound examination with the results of macro-microscopic investigation of distant GSV was carried out. The obtained data are evidence about the necessity of preoperative ultrasound mapping of varicose nodes and. the investigated inflows location. and. about their obligatory ligation for prevention of subcutaneous haematomas formation on the thigh after saphenectomy.